Ampliando a segurança de aplicações para a internet das coisas baseadas na plataforma FIWARE - Oliveira, Caio Thomás (2017)
The use of devices connected to the environment has been increasing in recent years. Using different communication technologies these devices allow to monitor and actuate in the environment. The Internet of Things (IoT) uses the Internet to interconnect such devices through to a wide range of applications. IoT is increasing its presence in business and home environments and the potential of this technology is being applied in different fields. However, this means a greater exposure of restricted information rising potential to threats its exploitation by attacks. Thus, security becomes a key requirement for the protection and prevention of cyberattacks to applications and devices. FIWARE Platform has an architecture of components responsible for interconnecting devices to IoT applications, decreasing complexity and providing a common set of services to developers. The IoT Agent is the component that allows integration of devices and its communication protocols with the rest of the platform. The version IDAS 5 of the platform presents some security gaps, so this work aims to incorporate end-to-end security services using encryption and access control in all NGSI requests. The main contribution was the implementation in NodeJs of DTLS 1.2 to support in the LWM2M/CoAP protocol and its addition to the IoT Agent. The work also allowed the IoT Agent support TLS in the communication of MQTT and NGSI. The source code of this work is open in the GitHub and can be used to support security services in other IoT communication protocols. Through an experimental evaluation it was possible to validate the implementation. It can be observed that the requests have had a small increase in terms of latency, but this cost is compensated by the increase of security in FIWARE based IoT Applications.